Pectic enzyme production by Fusarium oxysporum f. sp. cepae in onion bulbs as influenced by apoplast sugars and host cell walls - Holz, Gustav (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1983.